FRANZ WERFEL AS A CULTURAL CRITIC. INDIVIDUALISM, COLLECTIVISM AND THE MORAL-AESTHETIC TASK OF A POET - Knocke, Roy (Armenian Folia Anglistika, 2024)
This article is dedicated to the 90th anniversary of the heroic novel The Forty Days of Musa Dagh created by great Austrian writer and humanist Franz Werfel. With this novel Franz Werfel created a literary monument to the Armenian people. Werfel’s inspiration from his journey to Palestine and his encounter with Armenian orphans in Damascus are well known. Less known are his cultural-critical-philosophical essays that Werfel gave as lectures in the 1930s, framing his work on The Forty Days of Musa Dagh. These texts are densely formulated, often without references or plain argumentation. But they hold insights into Werfel’s moral demands on a poet, broaching that issue in the eras of communism, fascism, and genocide. This paper creates a moral-aesthetic profile that traces Werfel’s socially critical remarks with his view of the task of a poet and contrasts them with another contemporary view of a poet, that of Rainer Maria Rilke.